Formación de políticas públicas para la garantía de derechos humanos. - Sánchez Cubides, Pedro Alfonso; Higuera Jiménez, Diego Mauricio (Revista Pensamiento Americano)
This article deals with public policies as a means for the State to respect, protect, guarantee and promote human rights, through plans, programs, projects and activities, in whose training process the participation of the society is fundamental. Under the perspective of the Social Rule of Law, whose budget (presupuesto) is human dignity, the formation of public policies with more relevance should be oriented to the embodiment of rights, a process for which the rights-based approach is quite useful, whose elements are specified in the delimitation of the law, the liabilities of the State and the cross-cutting principles.